2019
DOI: 10.1016/j.jbo.2019.100219
|View full text |Cite
|
Sign up to set email alerts
|

Bone metastasis pattern of cancer patients with bone metastasis but no visceral metastasis

Abstract: BackgroundBone metastasis of cancer can be a result from systemic blood spreading or vertebral venous plexus spreading. Systemic blood pathway induced bone metastasis can happen in any bone in the body since the spreading is considered to be random. However, it remains unknown whether there is any pattern of vertebral venous plexus related bone metastasis. In this study, we explored bone metastasis patterns in patients whose primary tumors had been well identified.MethodsWe included 290 consecutive cancer pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…It would be very helpful and convenient if we could determine the clinical clues that could guide the search of the primary sites of CUP patients. Our team has reported that oligo bone metastasis may suggest the primary site to be in the neighboring area in patients without visceral metastasis [12]. Lymphatic spreading is a relatively early process in distant metastasis of cancer and nodal metastasis of most primary-known solid tumors follows sentinel lymph node (SLN) theory.…”
Section: Introductionmentioning
confidence: 99%
“…It would be very helpful and convenient if we could determine the clinical clues that could guide the search of the primary sites of CUP patients. Our team has reported that oligo bone metastasis may suggest the primary site to be in the neighboring area in patients without visceral metastasis [12]. Lymphatic spreading is a relatively early process in distant metastasis of cancer and nodal metastasis of most primary-known solid tumors follows sentinel lymph node (SLN) theory.…”
Section: Introductionmentioning
confidence: 99%
“…These uncommon sites for CUP presentation without visceral disease herald a unique subtype within the heterogeneous CUP entity and drive unique approaches in terms of their risk stratification and treatment. As both lymph node and bony metastases can develop far from a primary cancer, the location may not reliably provide an anatomic correlation in the search for the potential primary site and wide differential for putative primary cancers exists [3]. The workup of BCUP additionally poses unique challenges related to limited tissue availability and imaging sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…It would be very helpful and convenient if we could determine the clinical clues that could guide the search of the primary sites of CUP patients. Our team has reported that oligo bone metastasis may suggest the primary site to be in the neighboring area in patients without visceral metastasis 12 .…”
Section: Introductionmentioning
confidence: 99%